Hunter's moon : a novel in stories - Caputo, Philip (Henry Holt and Company, 2019)
Hunter<U+2019>s Moon is set in Michigan<U+2019>s wild, starkly beautiful Upper Peninsula, where a cast of recurring characters move into and out of each other<U+2019>s lives, building friendships, facing loss, confronting violence, trying to bury the past or seeking to unearth it. Once-a-year lovers, old high-school buddies on a hunting trip, a college professor and his wayward son, a middle-aged man and his grief-stricken father, come together, break apart, and, if they<U+2019>re fortunate, find a way forward. Hunter<U+2019>s Moon offers an engaging, insightful look at everyday lives but also a fresh perspective on the way men navigate in today<U+2019>s world.